Exploring the impact of oral health on the quality of life in older patients: a cross-sectional study - Nawaf H. Al Shammary (Nature Publishing Group, 2024)
Abstract Objective To investigate the significant impact of oral health on the quality of life of older individuals in Riyadh, Saudi Arabia, across various socioeconomic and demographic contexts. Methods A cross- sectional study was conducted, involving the distribution of a translated online questionnaire based on the OHQoL-UK® tool to evaluate oral health-related quality of life OHRQoL. This included utilizing the Oral Health Quality of Life Scale to assess overall quality of life. Results A total of 586 participants were involved in the study, with the majority being over 60 years old (77.1%). The mean score of OHRQoL was 3.79. The Social Dental Scale SDS had a mean score of 0.71. The General Oral Health Assessment GOHS scored 3.51 on average. The mean score of Dental Impact Profile DIP was 3.12. The Subjective Oral Health Status Indicators SOHSIs had a mean score of 3.82. The mean score of Oral Health Benefit of Life Inventory OHBLI averaged at 4.04, and Dental Impact on Daily Living DIDL scored an average of 4.05. The mean scores of OHRQoL and Oral Impacts on Daily Performance OIDP were 3.90 and 3.89 respectively. Cronbach's Alpha values ranged from 0.854 to 0.939, with an overall questionnaire reliability of 0.977, indicating a good reliability of the study's tool. Conclusion Older adults exhibited lower OHRQoL compared to younger adults, particularly influenced by factors such as health insurance coverage, monthly income, and educational level. It is essential to develop health programs specifically tailored for senior adults to safeguard their overall health and quality of life. Making health and medical insurance obligatory and accessible to all individuals is crucial for enhancing their QoL and reducing the diseases.